Impacto de la producción de petróleo crudo en el producto bruto interno de la región Loreto en el periodo 2007-2023 - García Gómez, Margarita Dolores (2025)
This research aimed to analyze the impact of crude oil production on the Gross Domestic Product (GDP) of the Loreto region during the period 2007-2023, using a quantitative methodology with a non experimental, longitudinal, and correlational approach. The study determined that the GDP growth in Loreto was not positive, with an average annual growth rate of -6.85%, indicating that oil production was declining year after year. In parallel, Loreto's Gross Domestic Product, measured by Gross Value Added (GVA), did experience a growth over the 17 years of this study, with an average annual growth rate of +5.05%, indicating that the Loreto economy experienced sustained growth during the given period. The study concluded that crude oil production did not have a significant impact on the Gross Domestic Product of the Loreto region during the period 2007-2023 period, as the variables are inversely related.